The UK's Great Demand and Supply Recession - Nick Jacob; Giordano Mion (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We revisit UK's poor productivity performance since the Great Recession by means of both a suitable theoretical framework and firm-level prices and quantities data for detailed products allowing us to both measure demand, and its changes over time, and distinguish between quantity total factor productivity (TFP-Q), i.e., the capacity to turn inputs into more physical output (number of shirts, liters of beer), and what we call revenue total factor productivity (TFP-R), i.e., productivity calculated using revenue (or value-added) as a measure of output and so the capacity to turn inputs into more revenue. This in turn allows us to measure how changes in TFP-Q, demand and markups ultimately affected revenue TFP, as well as labour productivity, over the Great Recession. Our findings suggest that the poor UK firms' productivity performance post-recession is due to both a weakening of demand and a decreasing TFP-Q pushing down sales, markups, revenue TFP and labour productivity.
Keywords: D24; L11; E01; O47; O52; 330; total factor productivity (TFP); revenue TFP; prices; demand; Great Recession; United Kingdom